Sustainable aquaculture in northern Ghana - International Water Management Institute (International Water Management Institute, 2024)
Explore the first successful tilapia harvest in Ghana's Nansoni community under the CGIAR Aquatic Foods initiative. See how local youths boost their incomes and plan for future cycles through sustainable aquaculture.